(untitled) (Моделювання, керування та інформаційні технології, 2023)
A numerical study of the dynamic contact problem is carried out by the method of orthogonal polynomials. А symbolic solution was found for the double transformants of the vertical displacements of the layered two-phase poroelastic liquid saturated base under the action of arbitrary vertical contact pressures. Numerical analysis was performed for the Rayleigh function and the components of displacements in the kernels of integrable functions. An example of calculating double integrals necessary to determine the contact pressures of two-phase soil under the base of the foundation is given.